PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP BRAND LOYALTY VASELINE HAND & BODY LOTION PADA MAHASISWA UNIVERSITAS NEGERI PADANG - Dini Novalia; Rose Rahmidani; Abel Tasman (Universitas Negeri Padang, 2018)
This research aims to know and prove how much the influence ofBrand Image and Brand Trust on Brand Loyaltytoward the studentsat Padang State University.This type of this research is causative. Population of this research werethe students of Padang State University. While the samples were taken as much as 100 respondents using purposive sampling method by Wibisono formula.Kinds of the data (sample) which was used in this research are primary and secondary . The analysis of data (sample) used pathtechnique by using SPSS program version 21.00. The results of this researchshow that: 1) Brand imagedoes not give thesignificant effecttowardbrand trust, 2) Brand imagedoes not give thesignificant effect towardbrand loyalty, 3) Brand trustgives significant effect towardbrand loyalty. Keywords: Brand Image, Brand Trust, and Brand Loyalty